The effect of surgical treatment of tubal pregnancy on concurrent intrauterine pregnancy after in vitro fertilization - Pei Cai; Mingxiang Zheng; Yangqin Peng; Yuyao Mao; Fei Gong; Hui Chen; Ge Lin; Yan Ouyang; Xihong Li (Scientific Reports)
Abstract Whether surgical treatment of tubal pregnancy affects the outcomes of concomitant live normally sited (eutopic) pregnancies is unknown. The purpose of this study was to investigate the outcomes of live eutopic singleton pregnancies following surgical treatment for concomitant fallopian pregnancies. A total of 446 patients who conceived tubal heterotopic pregnancies (HPs) via in vitro fertilization–embryo transfer and underwent surgical treatment to remove ectopic pregnancies (EPs) were included. For each study patient, one matched patient who conceived a live eutopic singleton pregnancy was selected randomly as a control. The rates of early miscarriage, late miscarriage, live birth, preterm birth, low birth weight and perinatal mortality were not significantly different between the study and control groups. The birth weight were also similar between these two groups. However, the caesarean section rate was significantly higher in the study group than that in the control group(P < 0.001). Additionally, laparotomy and laparoscopy for tubal HPs yielded similar pregnancy outcomes. Compared with controls, patients who conceived tubal pregnancies and concomitant live eutopic singleton pregnancies had similar pregnancy outcomes after proper surgical treatment of EPs. These findings can be used for counselling women who have conceived tubal HPs regarding the risks associated with surgical treatment.